Who do you want: Barabbas or Jesus?Power and empowerment in theological education - Hendriks, H Jurgens (Stellenbosch Theological Journal, 2016)
The article deals with theological education and leadership and questions the way power and empowerment functions in the church. It argues that theologically we follow the Barabbas choice and reject Jesus by not choosing the way of the cross and weakness. Our true identity needs to be, in following Philippians 2 and other passages, cruciform kenotic. The implications of such an identity for theological education and leadership are then put forward.